2005
DOI: 10.1111/j.1464-5491.2005.01499.x
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of diabetes mellitus

Abstract: Animal models have been used extensively in diabetes research. Early studies used pancreatectomised dogs to confirm the central role of the pancreas in glucose homeostasis, culminating in the discovery and purification of insulin. Today, animal experimentation is contentious and subject to legal and ethical restrictions that vary throughout the world. Most experiments are carried out on rodents, although some studies are still performed on larger animals. Several toxins, including streptozotocin and alloxan, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
417
0
33

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 562 publications
(456 citation statements)
references
References 144 publications
6
417
0
33
Order By: Relevance
“…We are surprised that there is not compensation for insulin deficiency with the single copy of Ins1 and with two copies of Ins1. However, a strain derived from the same colony as the NOD mouse, the NagoyaShibata-Yasuda mouse [9,10], a model of type 2 diabetes, which may share background genome with NOD [11,12], has no compensational hypertrophy of pancreatic islets despite increasing insulin resistance with ageing [9]. In addition, Kulkarni et al reported the importance of background genome in the induction of type 2 diabetes [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are surprised that there is not compensation for insulin deficiency with the single copy of Ins1 and with two copies of Ins1. However, a strain derived from the same colony as the NOD mouse, the NagoyaShibata-Yasuda mouse [9,10], a model of type 2 diabetes, which may share background genome with NOD [11,12], has no compensational hypertrophy of pancreatic islets despite increasing insulin resistance with ageing [9]. In addition, Kulkarni et al reported the importance of background genome in the induction of type 2 diabetes [13].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that greater insulin resistance for male mice with marginal insulin production leads to hyperglycaemia. In fact, most animal models of type 2 diabetes (including NagoyaShibata-Yasuda mice) show a high prevalence of type 2 diabetes in male mice [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The Australian National Primate colony has a long established non-human primate colony (Papio hamadryas), in which type 1 diabetes mellitus was induced by streptozotocin administered at an average 2 years of age [14]. Streptozotocin destroys the insulin-secreting beta cells of the pancreas and creates a hypoinsulinaemic, hyperglycaemic state that is similar to type 1 diabetes mellitus [15]. In many animal models, streptozotocin-induced diabetes mellitus has been shown to closely resemble that seen in humans [14] and such models are generally considered to be excellent for the study of type 1 diabetes [16].…”
Section: Introductionmentioning
confidence: 99%
“…Streptozotocin (STZ)-induced diabetes in rats is an interesting model because it triggers insulinopenic diabetes, which, as in human type 1 diabetes [7], involves the impairment of the immune system. Type 1 diabetes results from the selective destruction of insulin-producing beta cells in pancreatic islets [8].…”
Section: Introductionmentioning
confidence: 99%